Revitalisasi Permainan Tradisional: Upaya Meningkatkan Interaksi Sosial Anak dan Mengurangi Pengaruh Negatif Teknologi - Boby Syefrinando; Fibrika Rahmat Basuki; Krisna Suryanti (Jurnal Surya Masyarakat, 2026)
Traditional games play a crucial role in developing social skills and strengthening interaction among children. However, rapid technological advancement has shifted children's activities towards excessive use of digital devices, leading to a decline in social interaction. This Community Service Program (PKm) aims to revitalize traditional games to enhance children's social interaction and mitigate the negative effects of technology. The program was conducted at SDN 94/IV, Kota Baru District, Jambi City, involving 113 students as participants, along with teachers and university students as facilitators. The program employed the Participatory Action Research (PAR) method, enabling active involvement from all stakeholders at every stage of the activity. The implementation took place over three months, from October to December 2024. The results indicated increased student participation in traditional games and a reduction in gadget use outside of class hours. Additionally, social interaction among students improved, as reflected in their collaboration and communication during play. The revitalization of traditional games proved an effective way to reduce the negative impact of technology and restore a sense of togetherness among children.